Permeability and Selectivity of Sulfur Dioxide and Carbon Dioxide in Supported Ionic Liquid Membranes - 江滢滢 吴有庭 王文婷 李磊 周政 张志炳 (Chinese journal of chemical engineering, 2009)
Permeabilities and selectivities of gases such as carbon dioxide （CO2）, sulfur dioxide （SO2）, nitrogen （N2） and methane （CH4） in six imidazolium-based ionic liquids （[emim][BF4], [bmim][BF4], [bmim][PF6], [banim][BF4], [bmim][Tf2N] and [emim][CF3SO3]） supported on polyethersulfone microfiltration membranes are investigated in a single gas feed system using nitrogen as the environment and reference component at temperature from 25 to 45℃ and pressure of N2 from 100 to 400 kPa. It is found that SO2 has the highest permeability in the tested supported ionic liquid membranes, being an order of magnitude higher than that of CO2, and about 2 to 3 orders of magnitude larger than those of N2 and CH4. The observed selectivity of SO2 over the two ordinary gas components is also striking. It is shown experimentally that the dissolution and transport of gas components in the supported ionic liquid membranes, as well as the nature of ionic liquids play important roles in the gas permeation. A nonlinear increase of permeation rate with temperature and operation pressure is also observed for all sample gases. By considering the factors that influence the permeabilities and selectivities of CO2 and SO2, it is expected to develop an optimal supported ionic liquid membrane technology for the isolation of acidic gases in the near future.